Analysis Of The Integration Of a Hybrid Solar and Diesel Power Generation System In The Enggano Island Electricity System Using HOMER Simulation - Wahyudi Putra (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
The electrical system on Enggano Island still relies on diesel power plants (PLTD). Dependence on PLTD results in high operational costs and significant carbon emissions. This study analyzes the potential for integrating solar power plants (PLTS) with diesel power plants (PLTD) in a hybrid system configuration using HOMER Pro software. Input data includes electricity load profiles, solar radiation from NASA POWER, and technical and economic project parameters over a 25-year period. Simulation results indicate that the optimal configuration consists of a 2,316 kWp PLTS, 1,116 battery units, a 1,250 kW inverter, and a 1,000 kW generator, resulting in an LCOE of Rp2,936/kWh and a reduction in fuel consumption of over 30% compared to a diesel-only system. Renewable energy penetration reaches 33.7%, CO2 emissions are reduced by up to 1,500 tons/year, and the IRR reaches 28%. These results demonstrate that the hybrid system is feasible for implementation in 3T regions (Remote, Frontier, and Outer) to support the transition to clean energy.